System 1:
3x - 4y = 6
x + 4y = 18
Adding the two equations together to eliminate y:
4x = 24
x = 6
Substitute x back into the second equation to solve for y:
6 + 4y = 18
4y = 12
y = 3
Solution for System 1:
x = 6
y = 3
System 2:
3x - 4y = -3
4x - 3y = 10
Multiplying the first equation by 3 and the second equation by 4 to eliminate x:
9x - 12y = -9
16x - 12y = 40
Subtracting the first equation from the second to solve for y:
7x = 49
x = 7
Substitute x back into the first equation to solve for y:
3(7) - 4y = -3
21 - 4y = -3
-4y = -24
y = 6
Solution for System 2:
x = 7
y = 6
Use elimination to solve each system below.
system 1
3x-4y=6, x+4y=18
system 2
3x-4y=-3, 4x-3y=10
value of x
value of y
System 1
System 2
Enter the values of x and y in the solution for each system in the following table.
1 answer